Bio-Mathematical Concepts in DNA Splicing System - Heng, Fong Wan; Nor Haniza, Sarmin; Yuhani, Yusof (Shibaura Institute of Technology, 2010)
Splicing system is a formal characterization of the generative capacity of specified enzymatic activities operating on specified set of double-stranded DNA molecules.